SISTEM INFORMASI EMISI GAS RUMAH KACA TPA SAMPAH TELAGA PUNGGUR - Yodi Yodi (Teknik Informatika, 2019)
Telaga Punggur Solid Waste Landfill has been operating since 1997 with an area of ​​around 47 Ha. This landfill has actually replaced the landfill with a landfill control system, but in reality the field that is running is an open dumping system. To find out the amount of air pollution requires initial knowledge about pollutants that are very important for the anticipation, prevention and regulation of air emissions. One way to find out the emission distribution pattern is by using a comparison system using the online Gaussian Plume. Emissions by methane must be known because their effects can be felt 20-30 times greater than carbon dioxide. The results of this simulation can be used as a basis for making green belts in the landfill area. This regulates in SNI 03-3241-1994 on procedures for selecting the location of the final place of waste and PU Ministerial Regulation No. 19 of 2012 concerning guidelines for spatial planning of areas around the final place of waste requiring green belt areas in the landfill